Adaptasi budaya attention training technique untuk anak usia 5 – 6 tahun - Anggi Rengganis; Lenny Kendhawati; Marisa Fransiska Moeliono (University of Muhammadiyah Malang, 2022)
Delayed satisfaction for children is essential because self-regulation skills can be known through it. According to various studies, children who can delay getting pleasure immediately can avoid various unwanted actions in the future. The purpose of this study is to adapt culturally to the Attention Training Technique as one of the methods that are considered effective techniques in helping individuals to be able to control their thoughts, attention, and all actions in order to become more focused on activities. Attention Training Technique language adaptation process using Participatory and Iterative Process Framework for Language Adaptation (PIPFLA) method. The purpose of cultural adaptation of the Attention Training Technique is to be used by children aged 5-6years in Indonesia so that its application is expected to be more effective. Participants involved in the AttentionTraining Technique cultural adaptation trial were children aged 5-6 years with the condition that they did not have certain disorders selected based on convenience sampling techniques. The findings showed that attention training techniques with essential instruction in Indonesian could be understood and tested in children aged 5-6 years. Some notes that need to be considered are improvements in the duration of time and surveys regarding back sound noise variations that can be used during treatment.